Animal Symbols in the Works of the Seljuk Period; Ahlat Museum Example - YÜCEL, Mehmet; SANAL, Şule (Mersin Üniversitesi Tıp Fakültesi Lokman Hekim Tıp Tarihi ve Folklorik Tıp Dergisi, 2021)
Purpose: It is aimed to give information about the existence of animal motifs used in Turkish art during the Seljuk period in the works in Ahlat Museum, which houses examples in Ahlat, one of the important cities of the period, and the purpose of use of these motifs.Method: The animal symbols in the Ahlat Museum were evaluated, categorized according to their types, and the symbols used with various ornamental compositions were considered. 42 sample works were examined and photographs of animal symbols were taken. Then, the type of material on which the symbols were processed was determined, and the analyzed symbols were defined as a catalogue and analysed separately. Results: In this research carried out in the Ahlat Museum, 21 birds, 1 ram, 2 tigers, 3 fish, 1 rabbit, 1 gazelle, 1 donkey, 2 elephants, 2 horses, 42 animal figures, including 1 dragon, 1 lion, and 6 unidentified animals, were identified.Conclusion: As a result, it can be argued that during the Seljuk period, the Turks used animals effectively in their daily life, and this situation was reflected in their cultural activities, and animals were also given importance. Amaç: Selçuklular zamanında Türk sanatında kullanılan hayvan motiflerinin, dönemin önemli şehirlerinden birisi olan Ahlat’taki örneklerini barındıran Ahlat Müzesindeki eserlerde mevcudiyeti ve bu motiflerin kullanım amaçları hakkında bilgi verilmesi amaçlanmıştır.Yöntem: Ahlat Müzesi’nde bulunan hayvan sembolleri değerlendirilmeye alınarak, türlerine göre kategorize edilmiştir. Çeşitli süsleme kompozisyonları ile kullanılan semboller göz önünde bulundurularak, birbirinden farklı olan 42 adet örnek eser incelenmiş; hayvan sembollerinin fotoğrafları çekilmiştir. Ardından sembollerin işlendiği malzemenin cinsi belirlenmiş ve katalog şeklinde ayrı ayrı tanımlanarak çözümlenmesi yapılmıştır.Bulgular: Ahlat Müzesinde yapılan bu araştırmada, Müze envanterine kayıtlı 42 adet çanak, çömlek, mezar taşı veya çeşitli taş malzeme üzerine işlenmiş 21 kuş, bir koç, iki kaplan, üç balık, bir tavşan, bir ceylan, bir eşek, iki fil, iki at, bir ejder, bir aslan, altı adette tanımlanamayan hayvan olmak üzere 42 adet hayvan figürü tespit edilmiştir. Sonuç: Sonuç olarak, Selçuklu döneminde Türklerin hayvanları gündelik yaşamda etkili bir biçimde kullandıkları ve bu durumun kültürel aktivitelerine de yansıdığı, ayrıca hayvanlara önem verildiği iddia edilebilir.